2019
DOI: 10.1080/24750263.2019.1677790
|View full text |Cite
|
Sign up to set email alerts
|

Temperate mesophotic ecosystems: gaps and perspectives of an emerging conservation challenge for the Mediterranean Sea

Abstract: Mesophotic habitats, hosting benthic assemblages totally unknown and unexpected in the early 2000s, are attracting an increasing interest from scientists. Realizing that many long living and habitat forming species are playing a unique pocket of biodiversity in the frame of climate crisis, it is important to recognize the potential of the mesophotic zone in conservation strategies. The mesophotic zone is characterized by environmental factors generally more stable than the shallow counterpart; therefore, it re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 158 publications
(248 reference statements)
1
72
0
Order By: Relevance
“…In the Mediterranean Sea, particular attention is currently being paid to aphotic deep-sea habitats, such as seamounts, cold-water coral habitats, and submarine canyons (Mastrototaro et al, 2010;Bo et al, 2011aBo et al, , 2012aBo et al, ,b, 2015Cau et al, 2015;D'Onghia et al, 2015;Fanelli et al, 2017;Taviani et al, 2017Taviani et al, , 2019Chimienti et al, 2018bChimienti et al, , 2019Cardone et al, 2019). On the other hand, the mesophotic zone is located in the deeper photic zone, twilight zone, at a depth ranging from 30 to 40 m, which corresponds to the limit of conventional SCUBA diving, to >150 m, where there is sufficient sunlight penetration to support photosynthesis and living zooxanthellate corals (Kahng et al, 2014;Cerrano et al, 2019). In tropical and subtropical regions, mesophotic ecosystems are receiving scientific attention as they may offer refuge to shallow species due to their less altered environmental conditions (e.g., Baldwin et al, 2018;Bo et al, 2019;Sánchez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the Mediterranean Sea, particular attention is currently being paid to aphotic deep-sea habitats, such as seamounts, cold-water coral habitats, and submarine canyons (Mastrototaro et al, 2010;Bo et al, 2011aBo et al, , 2012aBo et al, ,b, 2015Cau et al, 2015;D'Onghia et al, 2015;Fanelli et al, 2017;Taviani et al, 2017Taviani et al, , 2019Chimienti et al, 2018bChimienti et al, , 2019Cardone et al, 2019). On the other hand, the mesophotic zone is located in the deeper photic zone, twilight zone, at a depth ranging from 30 to 40 m, which corresponds to the limit of conventional SCUBA diving, to >150 m, where there is sufficient sunlight penetration to support photosynthesis and living zooxanthellate corals (Kahng et al, 2014;Cerrano et al, 2019). In tropical and subtropical regions, mesophotic ecosystems are receiving scientific attention as they may offer refuge to shallow species due to their less altered environmental conditions (e.g., Baldwin et al, 2018;Bo et al, 2019;Sánchez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that, in Israel, the mesophotic zone still hosts healthy native assemblages, as also noted by Idan et al (2018). These assemblages lie at much lower temperatures, below 20°C year around, than the shallow subtidal, where summer temperatures exceed 30°C (analysis of the GLOBAL_ANALYSIS_FOR-ECAST_PHY_001_024 dataset at https://marine.copernicus.eu/) and may work as climatic refugia because they are less exposed to thermal anomalies and related mass-mortality events (Cerrano et al 2019). Therefore, they deserve strong conservation measures to protect their diversity, especially in areas like the easternmost Mediterranean Sea where climate warming and biological invasions are profoundly transforming the shallow shelf (Rilov et al 2020).…”
Section: Resultsmentioning
confidence: 52%
“…2 that there is currently very limited information on sponge abundance and percentage cover at depths below 20 m, irrespective of bioregion. While this is clearly related to accessibility issues, these mesophotic‐depth environments should be prioritised for future research, especially since a number of more recent studies have found high percentage cover (30–50%) of sponges at depths between 20 and 100 m in both temperate and tropical regions [see studies published after our literature search (June 2018) by Cerrano et al ., 2019, Bell et al ., 2019 and Lesser & Slattery, 2018; authors’ unpublished data for multiple sites in New Zealand]. The increasing availability of low‐cost ROVs should facilitate such exploration.…”
Section: Global Variation In Sponge Traitsmentioning
confidence: 99%